High velocity impact and armour design (eXPRESS Polymer Letters)
Improving combat survivability is the most important aspect of military technology. Hence the development of new lightweight armour systems is a key requirement. A large number of new high performance polymer fibres have been developed in recent years, which include Aramid fibres, polyethylene fibres and polypropylene fibres, amongst others, and have been applied to soft armour systems. To gain a fundamental understanding of which fibre type is the best for a specific application requires the development of techniques which can span all length scales. It has been widely recognised that multiscale modelling, which encompasses the full range of length and time scales, will be an important factor in the future design and testing of novel materials, and their application to armour design. In the present paper a new material damage model suitable for the simulation of impact on thin laminated panels fabricated from high performance fibres is implemented into the commercial ls-dyna® finite element code. The new material model links the mesoscale behaviour of the individual fibres to the macroscale behaviour within a conventional shell finite element. The implemented model is used in a parametric high velocity study to illustrate the applicability of the model to the design of thin armour panels.